The association of two common polymorphisms in miRNAs with diabetes mellitus: A meta-analysis - Li, Guixin (Medicine (Baltimore), 2019)
BACKGROUND: MicroRNAs (miRNAs) are small noncoding single-stranded RNAs with a length of ∼21 nucleotides. Single nucleotide polymorphisms (SNPs) may affect the function of miRNAs, resulting in a variety of disorders in vivo. Recently, diabetes mellitus (DM) has become a global healthcare problem, and several studies have reported that 2 common polymorphisms (miRNA 146a rs2910164 and miRNA 27a rs895819) are related to susceptibility to diabetes. Given that no consensus had been reached regarding the association of the 2 polymorphisms with diabetes, we conducted this meta-analysis. METHODS: Four databases (PubMed, EMBASE, Cochrane, and Web of Science) were searched up to January 9, 2019. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the association strength. Subgroup and sensitivity analyses were also performed. RESULTS: Six studies involving 2585 cases and 2435 controls for miR146a rs2910164 and 5 studies involving 2922 cases and 2781 controls for miR27a rs895819 were ultimately analyzed in our meta-analysis. Based on pooled results, no statistical significance in association between rs2910164 and diabetes in Caucasians, Asians, or type 2 diabetes was observed in any genetic models. Nevertheless, we found a significant correlation between miRNA27a rs895819 and diabetes in the homozygote model (CC vs TT: OR = 0.58, 95%CI [0.35,0.98]) and recessive model (CC vs CT + TT: OR = 0.59, 95%CI [0.36,0.97]). By performing subgroup analysis, we also observed that C allele conveyed a significant protective effect against diabetes development in Caucasians (C vs T: OR = 0.67, 95%CI [0.52,0.85]). CONCLUSION: In conclusion, this meta-analysis indicated that miRNA27a rs895819 might play a protective role in diabetes, and miRNA146a rs2910164 likely had no association with diabetes.